Comparison of Attention Levels in Primary School Students in Terms of Gender and Physical Activity - Dönmez, Meliha Uzun; İmamoğlu, Osman (Asian Journal of Education and Training, 2020)
The aim of this study was to compare attention levels of primary school students in terms of gender, school and physical activity. The study included a total of 301 primary school students, of whom 144 were female and 157 were male. Data were collected with Physical Activity Questionnaire and D2 Test of Attention. Pair-wise categorical comparisons were made with t test. There was a significant difference in scores for D2 Test of Attention and its subscales psychomotor speed and selective attention between genders (p<0.05), while the difference in special learning difficulty, concentration performance and physical activity was insignificant (p>0.05). Attention levels did not significantly differ between the students in state primary schools and those in private primary schools, either (p>0.05). The students were similar in physical activity and attention performance scores. To conclude, gender was found to play a significant role in psychomotor speed, selective attention level and total performance in D2 Test of Attention. All the students had moderate physical activity, which did not significantly differ between the students. In addition, attention levels were not different between state schools and private schools. However, the students with high physical activity were found to have higher attention performance. Therefore, primary school students should be enabled to have more physical activity to improve their attention.